Basis for the Establishment of the Financial Services Authority (OJK) as Regulator and Supervisor of Financial Services in Banjarmasin - Devia Hetty Hernany (Formosa Journal of Applied Sciences, 2023)
Continuous and stable supervision can be carried out by an independent institution such as Bank Indonesia or the Financial Services Authority. The basis for establishing the Financial Services Authority considers various aspects, especially technological aspects, where growth and development as well as financial service systems are increasingly needed by the public quickly and precisely. With the birth of the Financial Services Authority, regulation and supervision of financial service institutions can be easily carried out through one door, remembering that financial service institutions are not only banks but also non-bank financial service institutions and capital markets. With the formation of the OJK, it is hoped that it can support the interests of the financial services sector as a whole and increase the competitiveness of financial services institutions themselves in making contributions to national development.